2011
DOI: 10.1128/cvi.00389-10
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasma Antigen Clearance during Treatment of Histoplasmosis in Patients with AIDS Determined by a Quantitative Antigen Enzyme Immunoassay

Abstract: Clearance of Histoplasma antigen has been used as a marker for response to treatment of progressive disseminated histoplasmosis (PDH) in patients with AIDS. Advancements in Histoplasma antigen detection permit accurate quantification of antigen concentration. We compared the clearance of antigenemia and antigenuria during effective treatment of PDH. Urine and serum specimens were serially collected from patients with AIDS who were successfully treated for PDH as part of two prospective clinical trials. Samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 13 publications
1
40
1
Order By: Relevance
“…Antigenemia and antigenuria steadily declined during itraconazole therapy in dogs with blastomycosis (10). Antigen cleared more rapidly in serum than in urine, similar to what was observed in humans with histoplasmosis (8). The findings of the present study and these other reports support the rationale for a larger study using antigen to monitor therapy in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Antigenemia and antigenuria steadily declined during itraconazole therapy in dogs with blastomycosis (10). Antigen cleared more rapidly in serum than in urine, similar to what was observed in humans with histoplasmosis (8). The findings of the present study and these other reports support the rationale for a larger study using antigen to monitor therapy in humans.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, antigen tests are available for both of these fungal infections, can be performed on both urine and serum, and have superior sensitivities (83.3 to 91.8% for histoplasmosis and 92.9% for blastomycosis) (100,101). Also, a recent study showed that H. capsulatum antigenemia, but not antigenuria, decreases rapidly after clearance of the infection in AIDS patients with disseminated disease, thus having the potential to be used to monitor the response to treatment (102). Note that the H. capsulatum antigen test has a high sensitivity for both AIDS patients and patients with other causes of immune deficiency, such as solid organ transplant recipients (103), while its sensitivity for nonimmunocompromised individuals is relatively lower in cases of disseminated histoplasmosis (100).…”
Section: Other Fungal Infectionsmentioning
confidence: 99%
“…Also, unlike other diagnostic methods, monitoring of quantitative Histoplasma antigen values in urine and/or serum can be used to follow treatment responses and to monitor disease progression (13,14). The primary limitation of the MVista assay is the requirement that all specimens be submitted to MiraVista Diagnostics for testing, which can delay result reporting and affect patient management.…”
mentioning
confidence: 99%